Low-Level Laser Therapy: Potential and Complications: Low-Level Laser Therapy - Arjmand, Babak; Khodadoost, Mahmood; Jahani Sherafat, Somayeh; Rezaei-Tavirani, Mostafa; Ahmadi, Nayebali; Hamzeloo Moghadam, Maryam; Okhovatian, Farshad; Tavirani, Sina Rezaei; Rostami-Nejad, Mohammad (Journal of Lasers in Medical Sciences, 2021)
Introduction: Laser therapy has attracted experts’ attention in medical sciences. Many benefits of laser therapy are presented besides some complications. The present study, it is tried to present a new perspective of laser therapy in the various fields of medicine. Methods: Laser therapy-related articles which are combined with regenerative medicine, cosmetic, dentistry, neurodegenerative diseases, kidney, bone fracture, and vaginal function in the English language were searched through the google scholar search engine in the range of 2000-2021. After title screening, the abstracts were evaluated to access the full texts. Results: Basic concepts and various kinds of lasers that are applied in medicine were explained. Applications of laser therapy in various fields of medicine such as pain reduction, wound healing, regenerative medicine, dentistry, and several other body organs were highlighted and some complications were pointed. Conclusion: High potential of laser therapy for application in medicine implies a reconsideration of the laser properties and also styles of laser applications to improve the treatment and prevention of its side effects. DOI:10.34172/jlms.2021.42